Pengaruh Celebrity Endorsement, Brand Image dan Label Halal terhadap Minat Beli pada Kopi Torabika Gilus Mix - Suherman, Jajang; M. Sarusu, Armansyah (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
Based on data from topbrand-award.com, from 2022 to 2023, information was obtained that Torabika Gilus Mix coffee was lower than Good Day, Indocafe and Nescafe were in fourth position. This proves that people's buying interest in Torabika Gilus Mix coffee is very low. The aim of this research is to determine the influence of celebrity endorsement, brand image and halal labels partially and simultaneously on purchasing interest in Torabika Gilus Mix coffee products in Bandung. The type of research used is descriptive quantitative methods, research methods based on the philosophy of positivism, used to research certain populations or samples, data collection using research instruments, data analysis by means of description and statistics with the aim of testing predetermined hypotheses. The research results showed that celebrity endorsement was in the very agree or very good criteria, brand image was in the very good criteria. The halal label is in the criteria of strongly agree or very good, as well as buying interest in the criteria of agree or good. It can be concluded that celebrity endorsement, brand image and halal labels partially have a significant effect on buying interest in Torabika Gilus Mix products in Bandung.